Synthesis, physical-chemical properties, antimicrobial and antifungal activity of some 2-(2-((5-(adamantane-1-yl)-4-R-1,2,4-triazole-3-yl)thio)acetyl)-N-R1-hydrazine-carbothioamides - V. M. Odyntsova; A. M. Kamyshny; N. N. Polischuk (Zaporozhye State Medical University, 2017)
Special attention of pharmaceutical scientists is attracted to the creation of new potential substances. They select natural heterocyclic molecules that exhibit various types of pharmacological activity as basic structures. Adamantane derivatives, as well as a number of other framework compounds, in the vast majority are biologically active substances. This fact causes interest to the given classes of organic compounds as potential sources for the development of new drugs. Due to the high pharmacological action of 1,2,4-triazole derivatives, the combination of adamantane and 1,2,4-triazole in one molecule can lead to the formation of high-level pharmacological substances. The aim of this work is the synthesis of some 2- (2 - ((5- (adamantane-1-yl) -4-R-1,2,4-triasole-3-yl) thio) acetyl) -N-R1-hydrazine-carbothioamides, study of their physical and chemical properties, antimicrobial and antifungal activity. Materials and methods. The chemical names of the compounds are given in accordance with the requirements of the IUPAC nomenclature (1979) and the recommendations of the IUPAC (1993). Study of the physical and chemical properties of 2-(2-((5-(adamantane-1-yl)-4-R-1,2,4-triazole-3-yl)thio)acetyl)-N-R1-hydrazine-carbothioamides have been carried out on the certified and licensed equipment in the ZSMU physical-chemical laboratories. The melting temperature was determined by an open capillary method on the Opti Melt MPA 100. The elemental composition of the synthesized compounds was determined on the universal analyzer Elementar Vario L cube (CHNS) (standard - sulfanilamide). 1H NMR spectra were recorded on a spectrometer Varian Mercury VX-200 (1H, 200 MHz) in dimethylsulfoxide-d6solvent (tetramethylsilane - internal standard) and are decoded using ADVASP(tm)Analyzer program (Umatek International Inc.). Chromatographic mass spectral studies were performed on a gas-liquid chromatograph Agilent 1260 Infinity HPLC equipped with an Agilent 6120 mass spectrometer (ionization in an electric spray (ESI). Results. New 2-(2-((5-(adamantane-1-yl)-4-R-1,2,4-triazole-3-yl)thio)acetyl)-N-R1-hydrazine-carbothioamides are firstly synthesized, their structure is established by means of modern physical chemical methods of analysis (elemental analysis, IR-, NMR 1H-spectroscopy), and their individuality is done by HPLC-MS method. In all cases, the meanings of the investigated physical and chemical constants coincide with the estimated theoretical indicators. Determination of antimicrobial and antifungal activity was carried out by 2-fold serial dilutions method in liquid nutrient media. As a result of conducted investigations the compounds which levels of antimicrobial and antifungal action approaching, and in some cases exceeding comparison drug trimethoprim were revealed among the synthesized compounds. Conclusions. A compound of 2-(2-((5-(adamantane-1-yl)-4-phenyl-1,2,4-triazole-3-yl)thio)acetyl)-N-ethyl-hydrazine-carbothioamide occurred as the most active in relation to all test-strains among the synthesized substances, the force of antimicrobial and antifungal activity of it several times exceeds the comparison standard trimethoprim.